Collective identities beyond homogenisation: implications for justice and education. Issue 3 (3rd July 2022) - Drousioti, Kalli
ABSTRACT: In this article, I highlight what Ernesto Laclau and Chantal Mouffe's (re)conceptualisation of the plurality within identities implies for justice and education. Laclau and Mouffe (re)theorise the plurality of identities by framing and understanding identities within the wider theoretical context of discourse analysis and radical Democracy. I argue that the significance of this specific (re)theorisation of the plurality within identities for justice and education has not yet been tackled by the related educational-philosophical scholarship, not even by that which focuses on Laclau and Mouffe. As a first step, I provide a brief overview of Laclau and Mouffe's discourse theory and their approach to Democracy. Then, I show that, in their wider framework, one of the things that meaningfully connect discourse theory with radical Democracy is the theorisation of the plurality within identities. Finally, I suggest that acknowledging the plurality within any identity may offer important tools for expanding the scope of educational justice and for promoting justice in education. Amongst other things, by theoretically recognising the plurality and multi-dimensionality of collective identities, we obtain better insight into the pitfalls of homogenising identities and of cultivating reductive outlooks on identities in and through education, and encourage students' critical thinking and self-reflective stances toward subjectivities.